2022
DOI: 10.3390/ani12141839
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Body Size Determination Related Candidate Genes in Domestic Pig Using Genome-Wide Selection Signal Analysis

Abstract: This study aimed to identify the genes related to the body size of pigs by conducting genome-wide selection analysis (GWSA). We performed a GWSA scan on 50 pigs belonging to four small-bodied pig populations (Diannan small-eared pig, Bama Xiang pig, Wuzhishan pig, and Jeju black pig from South Korea) and 124 large-bodied pigs. We used the genetic parameters of the pairwise fixation index (FST) and π ratio (case/control) to screen candidate genome regions and genes related to body size. The results revealed 47,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 77 publications
0
4
0
Order By: Relevance
“…Genes activated by HIF-1 can enhance the oxygen delivery to tissues and promote cell metabolism to adapt to low oxygen levels, and HIF-1 negatively regulates the transcriptional regulation of various glycolytic pathway enzymes [ 42 ]. HIF-1 overexpression in hypoxic environments reduces the expression level of the myodifferentiation factor and myoietin, thus inhibiting myoblast differentiation [ 43 ]. Li et al [ 44 ] found that HIF-1α is important in the transition from oxidative metabolism to glycolysis in muscles.…”
Section: Discussionmentioning
confidence: 99%
“…Genes activated by HIF-1 can enhance the oxygen delivery to tissues and promote cell metabolism to adapt to low oxygen levels, and HIF-1 negatively regulates the transcriptional regulation of various glycolytic pathway enzymes [ 42 ]. HIF-1 overexpression in hypoxic environments reduces the expression level of the myodifferentiation factor and myoietin, thus inhibiting myoblast differentiation [ 43 ]. Li et al [ 44 ] found that HIF-1α is important in the transition from oxidative metabolism to glycolysis in muscles.…”
Section: Discussionmentioning
confidence: 99%
“…The association of the HMGA gene with growth and body weight has also been found in pigs and dogs. It was found that it is activated during early development, participates in the processes of cell division, and the body weight of the animal is highly correlated with HMGA expression [64][65][66]. The MSRB3 gene is an important member of the MSL gene family, which regulates the catalyzing effect of methionine-R-sulfoxide to methionine [67].…”
Section: Discussionmentioning
confidence: 99%
“…The GG genotype is associated with a larger live weight of animals, increased carcass yield, and the content of the pulp part in it, but also the ratio of protein and adipose tissue in meat preferred for dietary nutrition. The data obtained seem to be explained by the fact that the SNP at the rs268269710 position is located in close proximity to the HMGA2 and MSRB3 genes, for which a more pronounced association with growth energy in young animals has been described [62][63][64][65][66][67][68][69].…”
Section: Discussionmentioning
confidence: 99%
“…It is also characterised by slow growth, high intramuscular fat content, and superior meat quality [59] and is appreciated for its low feed consumption, convenient operation and management, and docile temperament. It is often studied in human medical research since it shows anatomical and physiological traits similar to humans [55,57,60]. Its SDG local risk status is "unknown".…”
Section: All Belted Breeds In Asia 221 Chinamentioning
confidence: 99%